Toward a Molecular Classification of Colorectal Cancer: The Role of Microsatellite Instability Status - Heinimann, Karl (Frontiers in Oncology, 2013)
Microsatellite instability (MSI) is the molecular hallmark of DNA mismatch repair (MMR) deficiency. Since its initial description in colorectal cancer (CRC) in 1993 and its association with Lynch syndrome, the most common inherited cancer predisposition world-wide, accumulating evidence suggests that MSI status may also be of concrete prognostic and predictive value in the management of sporadic CRC. This short review aims at providing a concise survey of the molecular basis and the multifaceted role(s) of MSI status in today’s clinical practice.